Pemanfaatan Sosial Media dalam Meningkatkan Exposure Brand dan Manajemen Usaha Hidoponik Hara House - Rasyid, Almer; Firdaus, Muhammad Rizki (Universitas Nusantara PGRI Kediri, 2023)
Making hydroponic plants is an easy and fun activity. This activity can also be done outdoors or indoors. Hara House has been a hydroponics business since 2020 in Malang City which has tremendous potential in supporting government programs related to food security. However, the limitations of the distribution network due to decreased demand due to the Covid-19 pandemic and the lack of optimal promotion through social media. The purpose of this community service is to assist our partner in market expansion by optimizing sosial media as a means of promotion. The proposed results indicate that partners able to optimize social media such as Instagram and Facebook as promotional media for market expansion to gain more profits.